Isolasi dan uji aktivitas enzim lipase termostabil dari bakteri termofilik pasca erupsi Merapi - Drajat Pramiadi; Evy Yulianti; Anna Rakhmawati (Jurnal Sains Dasar, 2014)
The usage of enzyme which comes from microorganism is more advantageous because it is easier to be multiplied in a relatively short time and does not need a large space, including lipase enzyme, which is often used in industries. The objective of this research is to isolate thermo stable lipase enzyme from thermophilic bacteria and to understand specific ativities. The thermophilic bacteria isolation is done using pour plate method. Selection of the bacteria producing lipase is shown from the presence of the biggest translucent zone around the colony on the olive oil medium with 0.1% Rhodamine-B. Two isolate produced by the biggest translucent zone are then continued by lipase enzyme isolation and activity tests. From 253 isolate, 43 isolate can grow on the medium that contains olive oil and 2 isolate shows translucent zone around the isolate, that is isolate 361 and isolate 213. The growth curve measurement for 24 hours shows that the exponential time is reached at the 10th hour for both isolates. The result of this research shows that temperature, pH, and enzyme isolate variation effects the enzyme activities. The enzyme activity tests show that on isolate 361, the best enzyme activities is obtained from incubation temperature of 50⁰C with pH 7, whereas for isolate 213, the best enzyme activities is reached when incubation temperature is 70⁰C with pH 6.   Key words: lipase, olive oil, thermophilic bacteria, thermo stable enzyme, enzyme activities